2011
DOI: 10.1245/s10434-010-1510-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Metastasis-Associated Protein 1 is Significantly Correlated with Tumor Angiogenesis and Poor Survival in Patients with Early-Stage Non-Small Cell Lung Cancer

Abstract: MTA1 protein overexpression is common in early-stage NSCLC and is significantly associated with tumor angiogenesis and poor survival. These findings suggest that MTA1 may have clinical potential as a promising predictor to identify individuals with poor prognostic potential and as a possible novel target molecule of antiangiogenic therapy for patients with early-stage NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…On the basis of the available data, it is very likely that MTA1 protein plays important and critical roles in the angiogenesis of a wide variety of human malignant tumors. The angiogenic activities of MTA1 protein in NSCLC has been reported in our previous study [31]. However, the roles of MTA1 protein in angiogenesis of NSCLC cell line have not yet been addressed.…”
Section: Discussionmentioning
confidence: 79%
“…On the basis of the available data, it is very likely that MTA1 protein plays important and critical roles in the angiogenesis of a wide variety of human malignant tumors. The angiogenic activities of MTA1 protein in NSCLC has been reported in our previous study [31]. However, the roles of MTA1 protein in angiogenesis of NSCLC cell line have not yet been addressed.…”
Section: Discussionmentioning
confidence: 79%
“…One of the key cancer promoting activities of MTA1 is its strong association with angiogenesis in human cancer [4246]. The underlying basis of MTA1’s role in angiogenesis includes its upregulation under hypoxic conditions in hypoxia-inducible factor-1α (HIF1α) - a key modifier of angiogenesis.…”
Section: Mta1’s Mechanism Of Action In Cancer Cellsmentioning
confidence: 99%
“…MTA1 is the founding member of the MTA family of coregulatory factors in transcriptional programs, and plays an integral role in nucleosome remodeling and histone deacetylation (NuRD) [14]. Overexpression of MTA1 is significantly associated with tumor progression and poor prognosis in NSCLC cells [15], and it has been demonstrated that the overexpression of MTA1 protein is common in early-stage NSCLC and is obviously related to tumor angiogenesis and poor survival [16]. A previous study demonstrated that MTA1 plays a key role in the regulation and mediation of the invasive phenotypes of lung cancer cells, and it has been reported that this regulation functions by altering the expression of miR [14].…”
Section: Introductionmentioning
confidence: 99%